2012
DOI: 10.1007/s10772-012-9139-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition from speech using source, system, and prosodic features

Abstract: In this work, source, system, and prosodic features of speech are explored for characterizing and classifying the underlying emotions. Different speech features contribute in different ways to express the emotions, due to their complementary nature. Linear prediction residual samples chosen around glottal closure regions, and glottal pulse parameters are used to represent excitation source information. Linear prediction cepstral coefficients extracted through simple block processing and pitch synchronous analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 42 publications
(34 reference statements)
0
30
0
Order By: Relevance
“…For example, prosodic speech features such as pitch and energy, can be extracted from each interval and are considered as local features [26], [30]. On the other hand, global features such as statistics, can be obtained from the whole speech utterance [22], [23], [16], which typically have a lower dimension than the local ones, leading to less computing time [13], [30].…”
Section: B Feature Extractionmentioning
confidence: 99%
“…For example, prosodic speech features such as pitch and energy, can be extracted from each interval and are considered as local features [26], [30]. On the other hand, global features such as statistics, can be obtained from the whole speech utterance [22], [23], [16], which typically have a lower dimension than the local ones, leading to less computing time [13], [30].…”
Section: B Feature Extractionmentioning
confidence: 99%
“…Moreover, their results indicated that spectral features from consonants may outperform the ones of vowels. Other approaches investigated combinations of features, such as the one of Koolagudi and Rao [14] who used global and local prosodic features and developed emotion recognition models using each feature separately, or combinations of features. Their experiments indicated that features may work in a complementary fashion towards higher recognition performance.…”
Section: Related Workmentioning
confidence: 99%
“…In [8] the authors have performed experiments with selected features, extracted from speech, that represent excitation source information and vocal tract information. The speech features have served as inputs to classifier based on either Gaussian Mixture Model (GMM), Support Vector Machine (SVM), or Auto-Associative Neural Network (AANN).…”
Section: A Emotional State Recognitionmentioning
confidence: 99%